Retaining the Thin Blue Line: What Shapes Workers' Willingness Not to Quit the Current Work Environment - Martin Gächter; David A. Savage; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2009)
The purpose of this study is to investigate the determinants of police officers\~O willingness to quit their current department. For this purpose, we work with US survey data that covers a large set of police officers of the Baltimore Police Department in Maryland. Our results indicate that more effective cooperation between units, a higher trust in the work partner, a higher level of interactional justice and a higher level of work-life-balance reduces police officers\~O willingness to quit the department substantially. On the other hand, higher physical and psychological stress and the experience of traumatic events are not, ceteris paribus, correlated with the willingness to leave the department. It might be that police officers accept stress as an acceptable factor in their job description.
Keywords: I10; I12; I31; J24; J81; Z13; 330; Willingness to Quit the Job; Turnover Rates: Job Satisfaction; Stress; Police Officers; Work-Life Balance; Fairness; Acceptance